(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article theoretically substantiates the need to organize and conduct an internal audit in budgetary organizations, form an internal audit summary, report and recommendations. The formation of the summary and report of the internal audit conducted in budgetary organizations was investigated. In budgetary organizations, author’s proposals have been developed to improve the formation of an internal audit summary, report and recommendations.